Emerging Applications of Synchrotron Radiation X‐Ray Techniques in Single Atomic Catalysts. Issue 11 (7th October 2022) - Song, Zhongxin; Li, Junjie; Davis, Kieran Doyle; Li, Xifei; Zhang, Jiujun; Zhang, Lei; Sun, Xueliang
Abstract: Single atom catalysts (SACs) can achieve a maximum atom utilization efficiency of 100%, which provides significantly increased active sites compared with traditional catalysts during catalytic reactions. Synchrotron radiation technology is an important characterization method for identifying single‐atom catalysts. Several types of internal information, such as the coordination number, bond length and electronic structure of metals, can all be analyzed. This review will focus on the introduction of synchrotron radiation techniques and their applications in SACs. First, the fundamentals of synchrotron radiation and the corresponding techniques applied in characterization of SACs will be briefly introduced, such as X‐ray absorption near edge spectroscopy and extended X‐ray absorption fine structure spectroscopy and in situ techniques. The detailed information obtained from synchrotron radiation X‐ray characterization is described through four routes: 1) the local environment of a specific atom; 2) the oxidation state of SACs; 3) electronic structures at different orbitals; and 4) the in situ structure modification during catalytic reaction. In addition, a systematic summary of synchrotron radiation X‐ray characterization on different types of SACs (noble metals and transition metals) will be discussed. Abstract : Synchrotron radiation technology is an important characterization method for identifying single‐atom catalysts. The detailed information of single atom catalysts obtained from synchrotron radiation is described through four routes: 1) the local environment of a specific atom; 2) the oxidation state of single atom catalysts; 3) electronic structures at different orbitals; and 4) the in situ structure modification during catalytic reaction.